2019
DOI: 10.1002/cdq.12194
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of High School Students’ STEM Career Aspirations

Abstract: Science, technology, engineering, and mathematics (STEM) fields have a need for recruiting and retaining a diverse workforce. Understanding students’ aspiration to STEM careers is important for supporting underrepresented populations. Data from a nationally representative sample (N = 20,010) of high school students who reported career aspirations were analyzed. Analyses revealed significant relations between students’ aspirations and demographic variables, and differences in aspirations based on students’ race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Careers included occupations that required a college degree (or above) and those that typically do not require college degrees. A similar measure of career expectations has been used in prior studies (Edwin et al, 2019; Gao & Eccles, 2020; Gottlieb, 2018; Starr & Simpkins, 2021). Changes from 9th to 11th grade could fall into four groups: students could (a) maintain STEM expectations, (b) switch from STEM to non‐STEM expectations, (c) maintain non‐STEM expectations, or (d)switch from non‐STEM to STEM expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Careers included occupations that required a college degree (or above) and those that typically do not require college degrees. A similar measure of career expectations has been used in prior studies (Edwin et al, 2019; Gao & Eccles, 2020; Gottlieb, 2018; Starr & Simpkins, 2021). Changes from 9th to 11th grade could fall into four groups: students could (a) maintain STEM expectations, (b) switch from STEM to non‐STEM expectations, (c) maintain non‐STEM expectations, or (d)switch from non‐STEM to STEM expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the cost of a college education, research still indicates that a college degree produces a positive and significant impact on individuals’ economic success and job satisfaction over a lifetime (Emmons, Kent, & Ricketts, 2019). Thus, there is a national education mandate that regardless of students’ postsecondary education (PSE) choices, all students leave school college‐and‐career ready and enroll in college (Bryan et al., 2016; Edwin et al., 2019; Malin, Bragg, & Hackmann, 2017). In this article, we use college to describe a number of PSE options including 4‐year bachelor's degree, 2‐year associate degree, and other PSE options.…”
mentioning
confidence: 99%
“…However, only the HSLS:09 includes a school counselor survey with multiple indicators suitable for examining how school counselors and their programs influence students’ college‐going pathways and decisions. Consequently, in a number of extant studies, scholars have begun to explore the associations and effects of a range of school counseling variables including school counselor expectations (Bryan et al., 2009; 2017); priority goals, use of time, hours spent on college readiness counseling (Engberg & Gilbert, 2014; Shi & Brown, 2020; Rangel & Ballysingh, 2020; Velez, 2016); frequently, student–counselor contact, visits, or talk (Bryan et al., 2011, 2017; Belasco, 2013; Velez, 2016); college and career readiness (CCR) activities (Edwin et al., 2019; Engberg & Gilbert 2014; Fitzpatrick, 2019; Fitzpatrick & Schneider, 2016; Rangel & Ballysingh, 2020); counselor caseloads (Goodman‐Scott et al., 2018; Shi & Brown, 2020; Woods & Domina, 2014); and number of counselors (Bryan et al., 2011; Robinson & Roksa, 2016) on students’ college‐going decisions, including receiving counseling for college admissions and for financial aid, career aspirations, applying to college, and college enrollment.…”
mentioning
confidence: 99%
“…Longitudinal studies from both the United Kingdom (Sheldrake, 2020) and the United States (Saw et al, 2018) indicated that adolescent girls were less likely than boys to have a STEM career aspiration to begin with, and to persist with that aspiration over time. Interestingly, a study by Edwin et al (2019) using data from ninth graders in the 2011 Wave of the U.S. High School Longitudinal Study found the opposite trend, with a significantly higher proportion of girls aspiring to STEM careers than boys. However, the taxonomy used for their coding included health careers in the STEM category, which may account for the discrepancy.…”
Section: Gender Differences In Career Aspirationsmentioning
confidence: 99%